ANALYSIS OF ULTRASTRUCTURAL CHANGES OF THE BLOOD CAPILLARIES IN DIFFERENT PARTS OF THE NEPHRON AT THE LATER STAGES OF EXPERIMENTAL HYPOTHYROIDISM DEVELOPMENT - Кузьменко, Ю.Ю. (World of Medicine and Biology, 2015)
The paper presents the results of a study of ultrastructural changes in capillaries of various parts of the kidney nephron through 50 days after total thyroidectomy in the experiment on laboratory animals. The part of the blood capillaries of the glomeruli are observed moderate ultrastructural change of the compensatory type, but a significant amount of blood capillaries is in the process of destruction; prevalence of dystrophic changes of endothelial cells increases; the majority of peritubular arterioles determined apoptotic changes. Thus, in the later stages of the development of experimental hypothyroidism in ultrastructural structure of blood capillaries of various parts of the nephron dystrophic and destructive processes prevail over compensatory.
Keywords: kidney; blood capillaries of the glomerulus; peritubular capillaries; nephron; thyroidectomy